THE USE OF VIRTUAL REALITY (VR) IN ENHANCING PUBLIC SPEAKING SKILLS IN RECEPTIVE ORAL LANGUAGE LEARNING - Annisa, Puan Suri Mira; Nasution, Rafika Dewi; Saragih, Bahagia; Nuran, Ade Aini; Sembiring, Fanny Rizki (JOURNAL OF LANGUAGE, 2025)
This study aims to examine how Virtual Reality (VR) can enhance students’ public speaking skills in Receptive Oral Language Learning. VR provides a realistic and interactive environment that allows learners to practice speaking without the pressure of a real audience. Through VR, students can engage in various scenarios, receive immediate feedback, and improve their confidence and fluency in public speaking. This research employed a mixed-method approach involving interviews, documentation, and questionnaires. The findings indicate that VR is an effective tool for improving both verbal and non-verbal communication. Quantitative results show that 80% of students strongly agreed and 20% agreed that VR enhances their public speaking performance. Qualitative feedback further revealed that VR practice reduced anxiety and increased learners’ motivation. However, challenges such as the high cost of VR equipment, limited accessibility, and health-related comfort issues were also identified. Overall, VR is proven to be a valuable pedagogical tool for improving students’ public speaking competence and receptive oral language learning outcomes.